Method and system for managing animal waste in an animal breeding farm - BA-ABBAD MAZEN A (2012)
The invention provides a method and system for managing animal waste produced in an animal breeding farm. The animal breeding farm is sealed from external atmosphere. The method includes collecting the animal waste from a plurality of animals in the animal breeding farm. The animal waste is then processed for obtaining fertilizers. The processing of the animal waste includes chemical treatment, thermal treatment, and aerobic digestion of the animal waste. The method further includes utilizing the fertilizers for growing a plurality of plants in one or more aeroponic units.